The Impact of GDP, Government Effectiveness, Globalization, and Carbon Emissions on ASEAN Tourism Receipts: An Empirical Study - Rohan, Ahmad; Suyanto, Suyanto (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of GDP, globalization, government effectiveness, and carbon emissions on International Tourism Receipts (ITR) across ten ASEAN countries during the period 2003-2018. Employing Fixed-effect model, Unit Root Tests, and Johansen Fisher Panel Cointegration techniques, the findings reveal that GDP and globalization have a significant positive effect on ITR. By contrast, government effectiveness and carbon emissions have a significant negative impact on tourism revenue. These results suggest that the success of the tourism sector is influenced not only by economic growth, but also by the quality of governance and environmental conditions. This study highlights the importance of efficient public policy, global openness, and environmental management in promoting sustainable tourism growth in the ASEAN region.